Vesseg - an open-source tool for deep learning-based atherosclerotic plaque quantification in histopathology images: brief report - Murray, Jacob; Pfeffer, Phillip; Seifert, Robert; Hermann, Alexander; Handke, Jessica; Kummer, Laura; Janßen, Henrike; Weigand, Markus A.; Schlemmer, Heinz-Peter; Larmann, Jan; Kleesiek, Jens Philipp (Arteriosclerosis, thrombosis, and vascular biology, 2021)
Download figureDownload PowerPoint